MANAGEMENT OF HYDROALLANTOIS IN A NON DESCRIPTIVE COW - RANGASAMY, S; RAJASUNDARAM, R C; SATHIAMOORTHY, T; SARATH, T (The Indian Journal of Animal Reproduction, 2023)
A case of hydroallantois in a non - descript cow and its successful therapeutic management has been reported.